Legal Frameworks and Their Role in Strengthening Democratic Governance - Rifa’i, Iman Jalaludin; Abdullah, Abdullah (Journal of Law and Social Politics, 2025)
Background: Democratic governance is fundamentally supported by the rule of law, which ensures transparency, accountability, and meaningful citizen participation in political processes. Nevertheless, in many jurisdictions, democratic institutions are weakened by fragile legal frameworks, judicial inefficiencies, and political interference, creating conditions that facilitate corruption and democratic backsliding. Objective: This study aims to analyze the role of law in strengthening democratic governance by examining how legal principles, institutional mechanisms, and constitutional safeguards contribute to the stability and effectiveness of democratic systems across different countries. Methods: The research adopts a qualitative approach using doctrinal legal analysis and comparative case studies. Legal documents, constitutional provisions, judicial decisions, and governance reports from various democratic nations are systematically examined to assess the relationship between legal frameworks and democratic governance. Results: The findings indicate that robust legal systems, independent judiciaries, and strong constitutional safeguards play a pivotal role in promoting democratic governance. Countries that provide effective legal protection for civil liberties and enforce checks and balances on executive power tend to demonstrate higher political stability, stronger public trust, and more resilient democratic institutions. Conversely, weak legal frameworks are closely associated with corruption, electoral manipulation, and the erosion of democratic norms. Conclusion: The study concludes that strengthening the rule of law is essential for sustaining democratic governance. A well-functioning legal system not only protects human rights and ensures governmental accountability but also enhances citizen participation. This research contributes to legal and political scholarship by offering an analytical framework to evaluate the effectiveness of legal systems in democratic governance and provides practical insights for policymakers and legal scholars seeking to strengthen democratic institutions globally.